2010
DOI: 10.4142/jvs.2010.11.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofArcanobacterium pyogenesisolated by post mortem examinations of a bearded dragon and a gecko by phenotypic and genotypic properties

Abstract: The present study was designed to identify phenotypically and genotypically two Arcanobacterium (A.) pyogenes strains isolated by post mortem examinations of a bearded dragon and a gecko. The A. pyogenes strains showed the typical biochemical properties and displayed CAMP-like synergistic hemolytic activities with various indicator strains. The species identity could be confirmed genotypically by amplification and sequencing of the 16S rDNA gene and, as novel target gene, by sequencing of the beta subunit of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 11 publications
2
34
0
4
Order By: Relevance
“…All T. pyogenes investigated in the present study were identified, comparable to previously described T. pyogenes [5]–[6]–[9], by determination of haemolytic and CAMP-like haemolytic reactions, by using various biochemical tests and genotypically using T. pyogenes specific parts of 16S–23S rDNA intergenic spacer region (ISR) [5] and T. pyogenes specific parts of superoxide dismutase A encoding gene sodA as molecular targets [9]. In addition the amplification of the known and putative virulence factor encoding genes, which had also been previously used to characterize various isolates of this bacterial species [6]–[9], yielded the presence of gene plo encoding pyolysin in 57 isolates, gene cbpA encoding a collagen-binding protein in one isolate, gene nanH encoding neuraminidase H in 39 isolates, gene nanP encoding neuraminidase P in 48 isolates and the fimbriae encoding genes fimA , fimC and fimE in 57, 53 and 52 isolates of the investigated isolates, respectively The phenotypical and genotypical properties are summarized in Table 1.…”
Section: Resultssupporting
confidence: 85%
“…All T. pyogenes investigated in the present study were identified, comparable to previously described T. pyogenes [5]–[6]–[9], by determination of haemolytic and CAMP-like haemolytic reactions, by using various biochemical tests and genotypically using T. pyogenes specific parts of 16S–23S rDNA intergenic spacer region (ISR) [5] and T. pyogenes specific parts of superoxide dismutase A encoding gene sodA as molecular targets [9]. In addition the amplification of the known and putative virulence factor encoding genes, which had also been previously used to characterize various isolates of this bacterial species [6]–[9], yielded the presence of gene plo encoding pyolysin in 57 isolates, gene cbpA encoding a collagen-binding protein in one isolate, gene nanH encoding neuraminidase H in 39 isolates, gene nanP encoding neuraminidase P in 48 isolates and the fimbriae encoding genes fimA , fimC and fimE in 57, 53 and 52 isolates of the investigated isolates, respectively The phenotypical and genotypical properties are summarized in Table 1.…”
Section: Resultssupporting
confidence: 85%
“…The pyolysin gene ( plo ) was detected using the primer pair and temperature conditions described elsewhere (Ülbegi‐Mohyla et al . ). Briefly, the PCR mixture (20 μ l) contained 0·1 μ mol l −1 of each primer (5′‐CGATCCCTCTGGTGTACTTGC‐3′, forward; 5′‐GCTTGACAAAAATCTGGCGTCC‐3′, reverse), 0·2 mmol l −1 dNTPs (Promega), 1·5 mmol l −1 MgCl 2 (Promega, Madison, WI), Green GoTaq ® Flexi Buffer (Promega), 0·5 U GoTaq ® Flexi DNA Polymerase (Promega) and 1 μ l DNA template.…”
Section: Methodsmentioning
confidence: 97%
“…The most typical clinical symptom of overt infection with T. pyogenes for all technological groups is the presence of abscesses in the subcutaneous tissue, organs or within muscles, which are only observable posthumously or during a post-mortem examination (Brinton et al 1993, Lawson et al 2001, Ertas et al 2005, Jost et al 2005, Ide et al 2006, Moore et al 2010, Ü lbegi-Mohyla et al 2010, Shahbazfar et al 2013. A factor that contributes to the development of purulent lesions is the production by T. pyogenes of pyolysine and serine protease.…”
Section: Suppurative Processes In Organs -The Most Typical Clinical Cmentioning
confidence: 99%